The combination of Alamouti coding with OFDM for the integration of the future MIMO radar and communication systems - Maciel, João Nuno Pinheiro (2018)
The demand for radio-frequency bandwidth is rising, with the growing number of users and applications. The radar and communication systems are two of main players in this regard and are central to make the IoT paradigm a reality. The separation of the radar and communication system is a waste of resources and the interference between the two systems is inevitable. On the other hand, their integration on a single hardware, enables the paradigm of dual functionality devices with communication and radar sensing capabilities fundamental to cope with the challenges of future IoT. In this dissertation, the integration of radar and communication systems is accomplished by using OFDM as a common waveform and the use of Alamouti coding enables both the achievement of spatial diversity, for the communication functionality, and of transmit signal orthogonality required to improve resolution, for the radar functionality. The evaluation of such methods as a way to achieve radar and communication integration was accomplished by developing a simulation platform, first only with the radar functionality, for SISO and MIMO configurations, and then with both radar and communication functionalities. The RadCom system developed present good performance, low complexity and so it is interesting for practical applications